The Role of Tree Mortality in Vitality Assessment of Sessile Oak Forests - Imre Berki; Ervin Rasztovits; Norbert Móricz; László Kolozs (South-East European Forestry, 2016)
Background and Purpose: The drought-induced vitality loss of sessile oak (Quercus petraea (Matt.) Liebl.) has been continuously observed in Hungary for more than three decades. The decrease in stand density as a consequence of drought-induced mortality has not been taken into consideration in most of the monitoring methods. Materials and Methods: Forest stands without any forest intervention during the last 30 years were selected. Quadrats were designated for the analysis in 18 sessile oak stands along a climatic transect in which foliage transparency and stand density were measured. Drought stress was defined by the water balance approach. By combining the foliage transparency and the relative stand density, a new cumulative assessment method of stand level vitality was introduced to get a more realistic picture about the effects of long-term drought (lasting for several decades) on the sessile oak forests in South-East Europe. Results: The calculated health status (100% - vital; 0% - dead) of the sessile oak stands was between 70-90% in the moist South-West Hungary and below 50% close to its xeric limit. The individual tree-based vitality assessment method gave considerably higher values on 17 out of 18 sites. Conclusions: Forest monitoring should also consider stand level-based tree mortality in oak forests while assessing health condition especially close to its xeric limit. The proposed new method provides a more realistic picture about the effects of climate change on sessile oak stands particularly for forest managers interested in changing in the wood stock of forests.